Perancangan Mesin Pencuci Telur guna Meminimalisir Tingkat Kerusakan pada UMKM Telur Asin Abhi - Atviono, Nafian Ramadhika; Murnawan, Hery (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Abhi Salted Eggs UMKM, located in Jombang Regency, produces salted eggs with a daily capacity of 850–1000 eggs from 1200 ducks. The production process, especially egg washing, faces significant challenges because it is still done manually. Problems that arise include long washing times, worker complaints due to exposure to soapy water, and egg damage rates reaching 7.14%–9.54%, causing losses of up to IDR 5,487,000 per month. To overcome these problems, an automatic egg washing tool was designed that can wash up to 20 eggs per cycle. Test results show that this tool is able to reduce the level of egg damage to 1% from 600 eggs tested, while increasing production capacity in the washing process. This innovation contributes to efficiency, reduced losses, and increased product hygiene, supporting the sustainability of Abhi Salted Eggs UMKM. Keywords: Egg Washer, QFD, Salted Eggs